Countering the Modern Metabolic Disease Rampage With Ancestral Endocannabinoid System Alignment - Pepper, Ian; Vinik, Aaron; Lattanzio, Frank; McPheat, William; Dobrian, Anca (Frontiers in Endocrinology, 2019)
When primitive vertebrates evolved from ancestral members of the animal kingdom and acquired complex locomotive and neurological toolsets, a constant supply of energy became necessary for their continued survival. To help fulfill this need, the endocannabinoid (eCB) system transformed drastically with the addition of the cannabinoid-1 receptor (CB1R) to its gene repertoire. This established an eCB/CB1R signaling mechanism responsible for governing the whole organism’s energy balance, with its activation triggering a shift towards energy intake and storage in the brain and the peripheral organs (i.e. liver and adipose). Although this function was of primal importance for humans during their prehistoric existence as hunter-gatherers, it became expendable following the successive lifestyle shifts of the Agricultural and Industrial Revolutions. Modernization of the world has further increased food availability and decreased energy expenditure, thus shifting the eCB/CB1R system into a state of hyperactive deregulated signaling that contributes to the 21st century metabolic disease pandemic. Studies from the literature supporting this perspective come from a variety of disciplines, including biochemistry, human medicine, evolutionary/comparative biology, anthropology, and developmental biology. Consideration of both biological and cultural evolution justifies the design of improved pharmacological treatments for obesity and Type 2 diabetes (T2D) that focus on peripheral CB1R antagonism. Blockade of peripheral CB1Rs, which universally promote energy conservation across the vertebrate lineage, represents an “evolutionary medicine” strategy for clinical management of present-day metabolic disorders.